Berberine inhibits proliferation and migration of colorectal cancer cells by downregulation of GRP78. Issue 2 (February 2020) - Gong, Chenxue; Hu, Xiao; Xu, Yingling; Yang, Jinhuan; Zong, Lei; Wang, Cui; Zhu, Ji; Li, Zhuoyu; Lu, Dezhao
Abstract : Human colorectal cancer (CRC), a highly malignant and metastatic carcinoma, is resistant to many present anticancer therapies. The inhibition of tumor survival and growth through receptor suppression is a promising way to treat CRC. The study aimed to investigate the effect of a natural plant triterpenoid, berberine (BBR), on SW480 cells and whether its role is mediated by Glucose-regulated protein 78 (GRP78). MTT assay, wound healing assay, and Annexin V-FITC assay were used to measure the effect of BBR on the proliferation, migration, and apoptosis of SW480 cells, respectively. Immunofluorescence and western blotting were used to evaluate both the downregulation of BBR on GRP78 and the role of GRP78 in the effect of BBR on SW480 cells. Our results revealed that BBR inhibited the proliferation and migration, as well as induced the apoptosis of SW480 cells, in a dose-dependent manner. BBR induced the dose-dependent inhibition of cell proliferation in HT-29 cells. BBR inhibited the expression of GRP78 and its localization on the cell surface. Moreover, BBR inhibited the expression of Bax, Bcl-2, c-Myc, and Vimentin and up-regulated the cytokeratin expression in SW480 cells. In addition, we found that the effects of BBR on cell proliferation, migration, and apoptosis in SW480 cells were reversed by the overexpression of GRP78. Our findings demonstrated that BBR inhibited the proliferation and migration and induced the apoptosis of SW480 cells by downregulating the expression of GRP78, and targeting GRP78 might be a potential way to develop the effective anticancer therapy.